Compton scatter imaging: A promising modality for image guidance in lung stereotactic body radiation therapy. Issue 3 (7th February 2018) - Redler, Gage; Jones, Kevin C.; Templeton, Alistair; Bernard, Damian; Turian, Julius; Chu, James C. H.
Abstract : Purpose: Lung stereotactic body radiation therapy (SBRT) requires delivering large radiation doses with millimeter accuracy, making image guidance essential. An approach to forming images of patient anatomy from Compton‐scattered photons during lung SBRT is presented. Methods: To investigate the potential of scatter imaging, a pinhole collimator and flat‐panel detector are used for spatial localization and detection of photons scattered during external beam therapy using lung SBRT treatment conditions (6 MV FFF beam). MCNP Monte Carlo software is used to develop a model to simulate scatter images. This model is validated by comparing experimental and simulated phantom images. Patient scatter images are then simulated from 4DCT data. Results: Experimental lung tumor phantom images have sufficient contrast‐to‐noise to visualize the tumor with as few as 10 MU (0.5 s temporal resolution). The relative signal intensity from objects of different composition as well as lung tumor contrast for simulated phantom images agree quantitatively with experimental images, thus validating the Monte Carlo model. Scatter images are shown to display high contrast between different materials (lung, water, bone). Simulated patient images show superior ( double) tumor contrast compared to MV transmission images. Conclusions: Compton scatter imaging is a promising modality for directly imaging patient anatomy during treatment without additional radiation, and it has the potential to complement existing technologies and aid tumor tracking and lung SBRT image guidance.